To be strategic in the new public sector, HR must remember its operational activities - Teo, Stephen; Rodwell, J. (John Wiley & Sons, Inc, 2007)
This article examines the level of operational and strategic involvement by human resource departments, the influence of HR departments, and the level of strategic integration as predictors of human resource management performance. Surveys from 146 senior line managers and HR executives in commercialized and non-commercialized public-sector agencies in Australia were the basis of organizational- and individual-level analyses. Results indicate positive relationships between the degree to which operational HR activities are transferred to line managers, HR influence, strategic integration, and the performance of the HRM function. Interestingly, no relationship was found between the level of strategic involvement by HR departments and the perceived performance of the function. Analysis of the individual-level data sup-ports the multiple-constituency approach to HRM, with differences in the evaluation of HRM by respondents from different job functions. The study highlights challenges faced by HR practitioners needing to be operational, to be valued strategically.